2014
DOI: 10.7150/ijms.7696
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Activities of Apolipoprotein M Promoter Are Associated with the Susceptibility to Coronary Artery Diseases

Abstract: The present study investigated the correlation among genetic polymorphisms of the proximal promoter region of apolipoprotein M (apoM) gene, the polymorphisms in relation to apoM expressions and the susceptibility to coronary artery diseases (CAD) in a Han Chinese population. Four common polymorphic sites, i.e., T-1628G, C-1065A, T-855C and T-778C, were confirmed, and a new deletion mutation C-724del was found, in 206 CAD patients and 209 non-CAD patients using direct DNA sequencing analyses. Occurrences of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
(37 reference statements)
2
11
4
Order By: Relevance
“…Subsequently, after the adjustment of susceptibility factors for CAD, the C allele was found to be an independent risk factor for the occurrence of ACS [ 25 ]. In addition, some other studies also obtained results similar to those mentioned above [ 18 , 22 , 23 , 26 ]. In contrast, Zheng et al found no statistically significant difference in distribution of 3 genotypes of ApoM rs805296 polymorphism, including TT, TC, and CC, between case and control groups, and concluded that rs805296 might not be correlated with the development of CAD [ 24 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Subsequently, after the adjustment of susceptibility factors for CAD, the C allele was found to be an independent risk factor for the occurrence of ACS [ 25 ]. In addition, some other studies also obtained results similar to those mentioned above [ 18 , 22 , 23 , 26 ]. In contrast, Zheng et al found no statistically significant difference in distribution of 3 genotypes of ApoM rs805296 polymorphism, including TT, TC, and CC, between case and control groups, and concluded that rs805296 might not be correlated with the development of CAD [ 24 ].…”
Section: Discussionsupporting
confidence: 81%
“…Initially, 81 records were identified through the computer search, and 36 remained after excluding 8 studies not on humans and 37 apparently irrelevant ones. Through the subsequent exclusion for reviews and letters (7), without full texts (3), duplicates (5), not about ApoM rs805296 polymorphism (8) and without original data (6), we eventually included 7 studies in the quantitative synthesis [ 18 , 21 – 26 ]. The primary features of eligible studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the present study had a number of limitations. Certain patients may receive lipid-lowering therapy prior to diagnosis with CAD, suggesting why the TC levels were lower in patients with CAD than in the control group subjects in the current study, which differed from previously published results [28]. We had a limited sample size to detect SNPs, and weak effects can be observed when considering multiple corrections.…”
Section: Study Strengths and Limitationscontrasting
confidence: 84%
“…The serum apoM concentration is significantly reduced in diabetic patients [ 6 ]. Single nucleotide polymorphism (SNP) T-778C, C-724del and T-855C in the proximal promoter region of apoM gene have significant associations with CAD and type-2 diabetes among Han Chinese [ 7 , 8 ]. Moreover, apoM is reduced in diabetic rats and exogenous insulin administrations could partially reverse the abnormal apoM expression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%